Differential Diagnosis of Post-Procedural Skin Lesions: A Case Report - Waghray-Penmetcha, Taruna; Li, Sam; Puranik, Rohit; Torres, Maria L. (Scientific Research, 2016)
Skin reactions caused by interventional pain procedures are well documented in literature, ranging from fistula formation to urticarial allergic reactions and infections. Burn lesions may also occur, however far less common; and as pain physician we must be cognizant of this possible complication and its etiologies. This is difficult in an outpatient setting where a patient cannot be regularly monitored, their adherence to prescribed therapies is unclear, and reporting is often done via phone, ancillary staff, and outside facility records. These compounding factors require clinicians to consider a broad differential and be comfortable with instituting myriad therapies or appropriately involve outside consultation for thorough patient care.
Keywords: Facet Arthropathy; Skin Lesions; Transcutaneous Electrical Stimulation; Capsaicin